ChemInform Abstract: Magnesium and Cadmium Containing Heusler Phases REPd2Mg, REPd2Cd, REAg2Mg, REAu2Mg and REAu2Cd. Issue 15 (24th March 2016) - Johnscher, Michael; Stein, Sebastian; Niehaus, Oliver; Benndorf, Christopher; Heletta, Lukas; Kersting, Marcel; Hoeting, Christoph; Eckert, Hellmut; Poettgen, Rainer
Abstract: Twenty‐eight new Heusler phases of title are prepared from the elements by induction heating (Nb ampoules, complex heating and annealing schedules).